2021
DOI: 10.3389/fmicb.2020.634640
|View full text |Cite
|
Sign up to set email alerts
|

The Prospective Synergy of Antitubercular Drugs With NAD Biosynthesis Inhibitors

Abstract: Given the upsurge of drug-resistant tuberculosis worldwide, there is much focus on developing novel drug combinations allowing shorter treatment duration and a lower toxicity profile. Nicotinamide adenine dinucleotide (NAD) biosynthesis targeting is acknowledged as a promising strategy to combat drug-susceptible, drug-resistant, and latent tuberculosis (TB) infections. In this review, we describe the potential synergy of NAD biosynthesis inhibitors with several TB-drugs in prospective novel combination therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 86 publications
(99 reference statements)
3
4
0
2
Order By: Relevance
“…As previously observed using a variety of INH concentrations [47], 1 µg/ ml INH significantly reduced the levels of nicotinamide adenine dinucleotide (NAD + ) (Figure 4B and Table 1). Other workers also found that 6.4 µg/ml INH alters levels of many metabolites [46].…”
Section: Resultssupporting
confidence: 80%
“…As previously observed using a variety of INH concentrations [47], 1 µg/ ml INH significantly reduced the levels of nicotinamide adenine dinucleotide (NAD + ) (Figure 4B and Table 1). Other workers also found that 6.4 µg/ml INH alters levels of many metabolites [46].…”
Section: Resultssupporting
confidence: 80%
“…Additionally upregulated in the gshT mutant strain was the nicotinamidase gene pncA . PncA is a functionally confirmed nicotinamidase in GAS ( 36 ) and plays an important role in the NAD + salvage and recycling pathway ( 37 ). Since GAS cannot de novo synthesize NAD + , it is dependent on salvage of the exogenous pyridine precursors, nicotinamide or nicotinic acid (vitamin B 3 ) ( 36 ).…”
Section: Resultsmentioning
confidence: 99%
“…SNP in nadD upstream region is associated with Pyrazinamide resistance. NadD is involved in NAD biosynthesis, which is targeted by Isoniazid, Pyrazinamide and some other promising antimycobacterial drugs [68].…”
Section: Discussionmentioning
confidence: 99%